Golgi bypass of ciliary proteins. (November 2018) - Witzgall, Ralph
Abstract: Primary cilia represent small, yet distinct compartments of the plasma membrane. They are speculated to exercise chemo- and mechanosensory functions and to serve as signaling hubs for crucial pathways such as the Wnt and hedgehog cascades. It is therefore necessary that specific integral membrane proteins, in particular sensors and receptors, are sorted to the cilium and not to the surrounding somatic plasma membrane upon being synthesized at the rough endoplasmic reticulum. Apparently no singular "zip code" for the primary cilium exists but rather several ciliary targeting signals whose biochemical and cell biological implications are just about being unravelled. Among the better understood proteins residing in the primary cilium is polycystin-2 which is mutated in patients suffering from autosomal-dominant polycystic kidney disease. A special case in the context of this review concerns the connecting cilium which serves as the trafficking pathway for proteins involved in visual sensation of retinal photoreceptor cells. In order to efficiently capture photons, the photopigments are organized in discs or membrane invaginations. Mutations in certain proteins involved in these processes lead to retinal degeneration and ultimately to blindness. One example is peripherin/rds which is mutated in the rds (r etinald egenerations low) mouse. The trafficking of peripherin/rds from the inner to the outer segment of photoreceptor cells by way of the connecting cilium also seems to diverge at the Golgi apparatus, and the routes of polycystin-2 and peripherin/rds may represent paradigms of ciliary proteins for the type IV pathway of unconventional protein "secretion". This review is part of a special issue of Seminars in Cell and Developmental Biology edited by Walter Nickel and Catherine Rabouille.